2016
DOI: 10.1515/aopf-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal and survival of stocked juvenile hatchery-reared Atlantic sturgeon (Acipenser oxyrinchus)

Abstract: Abstract. The post-stocking dispersal of juvenile Atlantic sturgeon (Acipenser oxyrinchus Mitchill) in the Wis³oka River (southern Poland) was investigated using biotelemetry. Thirty-five hatchery-reared juvenile A. oxyrinchus were tagged with radio or acoustic transmitters and tracked using mobile surveys and fixed receivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
(2 reference statements)
1
5
0
Order By: Relevance
“…A record low water discharge and as a result a slower flow velocity in 2015 compared with the preceding year in the Šventoji River most likely determined a significantly lower migration speed as only these two factors differed significantly between years. The same pattern was observed in other Baltic basin rivers of similar size (Kapusta et al, ). However, downstream migrations in the same migration sections in autumn 2015 were significantly faster than in summer 2012 and summer 2013.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A record low water discharge and as a result a slower flow velocity in 2015 compared with the preceding year in the Šventoji River most likely determined a significantly lower migration speed as only these two factors differed significantly between years. The same pattern was observed in other Baltic basin rivers of similar size (Kapusta et al, ). However, downstream migrations in the same migration sections in autumn 2015 were significantly faster than in summer 2012 and summer 2013.…”
Section: Discussionsupporting
confidence: 86%
“…Radio telemetry data revealed that 9–10‐month‐old sturgeon migration speed in rivers varied significantly over years and within different migration sections. The observed migration speed in the current study and in other rivers in the Baltic region was extremely variable between individuals (Fredrich, Kapusta, Ebert, Duda, & Gessner, ; Kapusta, Morzuch, Duda, Bogacka‐Kapusta, & Kolman, ; Kapusta, Morzuch, & Kolman, ). Altogether, these findings support a divergent migration behavior hypothesis among sturgeons (Kessel et al, ).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Upon release, juveniles tend to disperse after some time only. Following release, they reveal high densities near the site of release (Kapusta, Morzuch, Duda, -Kapusta, & Kolman, 2016), which often attracts temporary aggregations of predators (Johnson & Ringler, 1998). The very high rates of post-release mortality experienced in most restocking programs undermine these activities and raise major economic and welfare concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Atlantic sturgeon do not exhibit shoaling behaviors, and after they are released in the natural environment they migrate downstream individually (Fredrich, Kapusta, Ebert, Duda, & Gessner, ). However, it takes them some time to disperse after release, and during this time they remain in relatively close proximity to one another near the release site for several hours (Kapusta, Morzuch, Duda, Bogacka‐Kapusta, & Kolman, ), which can increase their exposure to predation, especially since temporary aggregations of predators are observed at release sites (Johnson & Ringler, ). Studies conducted to date (Crossman, Scribner, Forsythe, & Baker, ; French et al, ; French, Graeb, Chipps, & Klumb, ; Gadomski & Parsley, 2005b) demonstrate that juvenile sturgeons are generally less susceptible to predation than most alternative preys, but they can be affected by the direct or indirect impact of benthic predators.…”
Section: Introductionmentioning
confidence: 99%